Zygaenid moths of Australia : a revision of the Australian Zygaenidae, (Procridinae: Artonini) - Tarmann, Gerhard M. (Monographs on Australian Lepidoptera ;, 2004)
Coverage of zygaenid morphology, biology, phylogeny, classification and in-depth treatment of the genera and species present in Australia.